PENGARUH METODE GLENN DOMAN TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 4-6 TAHUN DI RA PERWANIDA 2 PALEMBANG - Ulandari, Hikma; Yuniar, Yuniar; Cindrya, Elsa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low early reading skills of children aged 4–6 years at RA Perwanida 2 Palembang, characterized by difficulties in recognizing letters and assembling simple syllables. The primary objective of this study is to determine the significant influence of using the Glenn Doman method on children's early reading abilities. The research method employed is quantitative with a Pre-Experimental design, specifically the One Group Pretest-Posttest model. The research population included all students in class B1, totaling 19 children, with samples selected using a purposive sampling technique. Data were collected through structured observations and performance tests, then analyzed using the Paired Sample T-Test via statistical software. The results showed a significant increase in reading ability, evidenced by the rise in the mean score from 52 in the pretest to 78 in the posttest. Statistically, a significance value (2-tailed) of 0.000 was obtained, which is lower than the significance level of 0.05, leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). This indicates that the Glenn Doman method, based on pictorial word cards, is effective in stimulating children's basic literacy development visually and enjoyably. Through repetitive and interactive stimulation, children became more enthusiastic, focused, and confident in pronouncing words. In conclusion, the Glenn Doman method has a positive impact and can serve as an innovative alternative learning strategy for teachers to improve the quality of early childhood reading skills. Keywords: Glenn Doman Method, Early Reading, Early Childhood Education, Word Cards, Language Skills.